PREVALENCE OF GASTROINTESTINAL PARASITES IN THOROUGHBRED HORSES (EQUUS CABALLUS) DURING THE PERIOD OF 2011 IN THE RACETRACK“LA RINCONADA”, CARACAS, VENEZUELA - Morales B, Abelardo A. (2012)
Eight hundred and ninety four 2-year old thorough bred race horses (Equus caballus), 400 males and 494 females from breeding centers in the central region of Venezuela were studied for intestinal parasites. Stool specimens were examined using McMaster flotation technique (Willis-Molloy) during the quarantine period in 2011 at the Racetrack "La Rinconada" Caracas, Venezuela. Strongyle eggs were found in 553 horses, Parascaris equorum eggs in 69 specimens, and Oxyurus equi in 8. A total of 264 specimens were negative. The highest percentage of parasites observed was 62% Strongyles, 8% P. equorum, Oxyurus equi 1% and 30% were negative for the presence of parasite eggs. The presence of equine infected with strongyles remained within the range of 600-1900 HPG, while in P. equorum, HPG was 350-800 and O. equi had a mean of 400 HPG. These results suggest flaws in the health plan specifically to control parasites. It is possible that parasite resistance to conventional treatment as well as associations with climate changes may be related. In conclusion, we report a high prevalence of gastrointestinal parasites in Thoroughbred racing horses during the quarantine period at the Hippodrome "La Rinconada" Caracas, Venezuela.